Cell‐laden Microengineered and Mechanically Tunable Hybrid Hydrogels of Gelatin and Graphene Oxide. (1st September 2013) - Shin, Su Ryon; Aghaei‐Ghareh‐Bolagh, Behnaz; Dang, Tram T.; Topkaya, Seda Nur; Gao, Xiguang; Yang, Seung Yun; Jung, Sung Mi; Oh, Jong Hyun; Dokmeci, Mehmet R.; Tang, Xiaowu (Shirley); Khademhosseini, Ali
<x xml:space="preserve">Abstract</x> Incorporating graphene oxide inside GelMA hydrogels enhances their mechanical properties and reduces UV‐induced cell damage while preserving their favorable characteristics for 3D cell encapsulation. NIH‐3T3 fibroblasts encapsulated in GO‐GelMA microgels demonstrate excellent cellular viability, proliferation, spreading, and alignment. GO reinforcement combined with a multi‐stacking approach offers a facile engineering strategy for the construction of complex artificial tissues. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>